Android Studio Giraffe Essentials - Java Edition: Developing Android Apps Using Android Studio 2022. 3. 1 and Java - Smyth, Neil (Payload Media, 2023)
Fully updated for Android Studio Giraffe, Android Jetpack and the modern architectural guidelines and components, the goal of this book is to teach the skills necessary to develop Android-based applications using the Java programming language.